Key Attributes of Change Agents for Successful Technology Adoptions in Construction Companies: A Thematic Analysis - Afiqah, R. Radzi; Hashim, R. Bokhari; Abdul Rahimi, Abdul Rahman; K. Ayer, Steven (ASCE, 2019)
The construction industry has been criticized for lower productivity than other sectors, which may be influenced in part by its historical resistance to change in adopting new technologies. Therefore, it is common for organizations to have dedicated change agents to support effective technological adoption. This study aimed to identify the key attributes of change agents that influence the success of adopting new technologies in construction companies. To achieve this objective, industry practitioners in the United States provided responses to open-ended questions and the answers were analyzed to identify common themes. The significant findings include: (1) change agents’ personality is the most frequently reported attribute that contributes to their effectiveness, and (2) human-related attributes have a larger role in successful technological adoptions compared to organizational- and technical-related attributes in change agents. This paper contributes to the body of knowledge by identifying the frequency of attributes that are reported to impact the effectiveness of change agents in industry.